Answer: The answer is A. Step by step explanation: =(32+7)−(3−2) =(32+7)−3-2 =32+7−3+2 =32+9−3 =32−3+9 Log in to Reply

Answer: A. 3×2 – 3x + 9 Step-by-step explanation: * means multiplied (3×2 + 7) – (3x – 2) – (3x – 2) is really -1 * (3x – 2) so -1 * (3x – 2) is -3x + 2 so (3×2 + 7) – (3x – 2) = (3×2 + 7) – 3x + 2 = 3×2 – 3x + 9 Log in to Reply

Answer:The answer is A.

Stepbystepexplanation:=(32+7)−(3−2)

=(32+7)−3-2

=32+7−3+2

=32+9−3

=

32−3+9Answer:A. 3×2 – 3x + 9

Step-by-step explanation:* means multiplied

(3×2 + 7) – (3x – 2)

– (3x – 2) is really -1 * (3x – 2)

so

-1 * (3x – 2)

is

-3x + 2

so

(3×2 + 7) – (3x – 2) =

(3×2 + 7) – 3x + 2 =

3×2 – 3x + 9